A comparison of using bulk and incremental isotopic analyses to establish weaning practices in the past. Issue 1 (1st January 2017) - King, Charlotte L.; Millard, Andrew R.; Gröcke, Darren R.; Standen, Vivien G.; Arriaza, Bernardo T.; Halcrow, Siân E.
ABSTRACT: The use of incremental carbon and nitrogen isotopic analysis is gaining momentum as a way of establishing infant feeding practices in the past. Here we examine the differences in information gleaned through incremental isotopic techniques applied to individuals, relative to more commonly-used bulk isotopic sampling of a cross-section of a population. We use bulk sampling methods, which use bone collagen isotope values from multiple individuals, to construct Bayesian weaning curves for our samples. We then compare these results to individual weaning times established through incremental isotopic analysis of single deciduous teeth. Our results highlight that in contexts with high adult dietary variation it may not be possible to interpret weaning behaviour using cross-sectional techniques, and incremental isotopic analysis may be the only way of interpreting weaning behaviours. Our findings also suggest that cross-sectional analyses are the most useful way of creating population-scale interpretations of weaning behaviour within a sample. Incremental techniques, however, are necessary if we want to tell individual weaning stories and investigate the variation in infant-feeding present within the past.